Constraints on the economic development of Zambia - Elliott, Charles (Nairobi : Oxford University Press, 1971)
This book examines constraints that had confronted Zambia prior to 1970s. The book covers industrial relations; wages; financial constraints; foreign exchange constraints; mining constraints; agriculture constraints and manufacturing sectors constraints that had hindered economic development in Zambia.
Includes bibliographical references.
lje 23/01/2018
Loans
Keywords: Economic development; Economic history; Industries; Zambia